Polinomial Kromatik Graf Bunga - Risang Narendra (UJMC (Unisda Journal of Mathematics and Computer Science), 2022)
In this study, the class of a graph called Flower Graph was discussed. Flower Graph is a special way in a graphic. A graph G is called a flower chart-. This graph will be symbolized by . Then, it is defined by a flower chart-, with the petal to which in a flower graph-, by -petal removed, for . Flower graphics-: with petal as much as is denoted by . Chromatic polynomial is the amount of forms to color the point in graph G with color, where there are no two points that fit to obtain the same color. In the end, using the reduction theorem, the chromatic polynomial theorem of the Sikel chart and the chromatic polynomial graphic of the chromatic polynomial tree of a flower chart obtained.